2009
DOI: 10.1097/ta.0b013e3181b840e8
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Craniectomy With Craniotomy: What Role in the Management of Severe Traumatic Brain Injury?

Abstract: CE was used in patients with more severe injuries, and particularly in those with more severe head injuries. When adjusted for injury severity, CE was not associated with worsened survival, and therefore may reasonably be included in the armamentarium of neurotrauma care. Use of CE by our neurosurgeons, however, varied significantly. These findings underscore the need for practice guidelines based on randomized trials to fully evaluate the role of CE in the management of TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
2
17
2
2
Order By: Relevance
“…A number of studies have demonstrated that the timing of surgical intervention is a major determinant of the outcome of subdural hematoma treatment (4,9). The recommended timing for evacuation of a hematoma is within 4 h of onset; delays past this critical window of time are associated with neuronal loss and poorer outcomes in a number of neurological conditions, including subdural hematomas and strokes (4,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have demonstrated that the timing of surgical intervention is a major determinant of the outcome of subdural hematoma treatment (4,9). The recommended timing for evacuation of a hematoma is within 4 h of onset; delays past this critical window of time are associated with neuronal loss and poorer outcomes in a number of neurological conditions, including subdural hematomas and strokes (4,10).…”
Section: Discussionmentioning
confidence: 99%
“…The recommended timing for evacuation of a hematoma is within 4 h of onset; delays past this critical window of time are associated with neuronal loss and poorer outcomes in a number of neurological conditions, including subdural hematomas and strokes (4,10). Trepanation and drainage is a rapid method for stabilizing a patient with an early-stage subdural hematoma who is unable to receive surgery in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid placement of a single burr hole can be used in certain circumstances in the management of acute brain trauma; for example, in case of a rapidly enlarging temporal AEDH of arterial source that jeopardizes the patient's life, placement of a burr hole over the temporal region can save the patient's life while the surgeon completes the craniotomy for hematoma evacuation (Paci et al, 2009). Exploratory burr holes, once used frequently, are now employed to a lesser extent, because lesions can be rapidly identified through CT imaging (Cordobés et al, 1981).…”
Section: Use Of Burr Holes In the Surgical Management Of Traumatic Brmentioning
confidence: 99%
“…However, in some instances a single burr hole may be implemented for rapid decompression (Paci et al, 2009), or as an exploratory measure (Cordobés et al, 1981).…”
Section: Introductionmentioning
confidence: 99%